1980
DOI: 10.1007/bf00426516
|View full text |Cite
|
Sign up to set email alerts
|

Oral dyskinesia in brain-damaged rats withdrawn from a neuroleptic: Implication for models of tardive dyskinesia

Abstract: Rats with ablated frontal sensorimotor cortex and one with ablated sensorimotor connections to forebrain showed more vacuous chewing movements following 6-week chronic administration of a neuroleptic than did occipitally damaged rats or normal controls who were treated in the same way. The effect was still present 1 month after withdrawal. It was not clearly enhanced by subsequent treatments. Other behaviors (e.g., walking, rearing, or grooming) were not similarly affected by drug withdrawal. Additional result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…In most rats, these vacuous jaw movements were evident with the first administration of HP. These results are consistent with other reports showing that acute or sub-chronic administration of a neuroleptic can increase vacuous jaw movements (Glassman and Glassman 1980;Rosengarten et al 1983;Rupniak et al 1985Rupniak et al , 1986Jicha and Salamone 1991). However, the present findings remain controversial in view of the fact that some studies have failed to observe vacuous jaw movements in the first few hours after acute neuroleptic injection Ellison et al 1987).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In most rats, these vacuous jaw movements were evident with the first administration of HP. These results are consistent with other reports showing that acute or sub-chronic administration of a neuroleptic can increase vacuous jaw movements (Glassman and Glassman 1980;Rosengarten et al 1983;Rupniak et al 1985Rupniak et al , 1986Jicha and Salamone 1991). However, the present findings remain controversial in view of the fact that some studies have failed to observe vacuous jaw movements in the first few hours after acute neuroleptic injection Ellison et al 1987).…”
Section: Discussionsupporting
confidence: 92%
“…Gunne et al (1986) observed that several antipsychotic drugs failed to produce spontaneous chewing movements in the first few hours after acute administration. However, in some studies vacuous jaw movements have been reported to occur after acute or sub-chronic administration of neuroleptics (Glassman and Glassman 1980;Rosengarten et al 1983;Rupniak et al 1985Rupniak et al , 1986. In discussing the possible relation between vacuous chewing and tardive dyskinesia, Waddington (t990, p 439) has noted that "the greatest problems of interpretation are provided by those studies which have reported the emergence of orofacial movements very early in the course of neuroleptic treatment".…”
Section: Administration Of Da Antagonists or Cholinomimetic Drugs Indmentioning
confidence: 94%
“…Long-term administration of neuroleptics in rats increases perioral behaviors that have been termed vacuous chewing Offprint requests to: H.C. FiNger movements (VCMs) (Glassman and Glassman 1980;Gunne et al 1982;Waddington et al 1983). This phenomenon has been proposed as a potential model for neurolepticinduced tardive dyskinesia in humans (see Gunne et al 1982).…”
mentioning
confidence: 98%
“…An even more severe problem is that several laboratories have reported that "vacuous oral movements" occur in rodents as soon as 24 h after an acute injection (Glassman and Glassman, 1980;Rosengarten et al, 1983;Rupniak et al, 1985). Thus, in some situations, they are clearly not tardive in appearance.…”
Section: Rodent Studiesmentioning
confidence: 94%